2020
DOI: 10.1007/s00787-020-01647-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects and moderators of the Olweus bullying prevention program (OBPP) in Germany

Abstract: Bullying is a common and significant risk factor for mental and physical health problems. The aim of the outlined study was to evaluate the German version of the Olweus Bullying Prevention Program (OBPP) and to investigate potential moderators of its effectiveness. 23 schools started with the implementation and all students were invited to complete the Olweus Bullying Questionnaire annually. For our analyses, the data from grades 5 to 9 were used (t0: n = 5759; t1: n = 5416; t2: n = 4894). 16 out of the 23 sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
0
19
2
1
Order By: Relevance
“…But even after termination of experienced bullying victimization during a bullying prevention program, individuals lacked full recovery from mental health problems and presented with ongoing reduction of quality of life. Interestingly, we did not observe a decline in psychopathology despite successful implementation of bullying prevention (Ossa et al, 2020). While bullying declined from 8.00% to 5.11% within two years, the observed level of emotional problems, total difficulties, non-suicidal self-injury, and suicidality remained relatively stable.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…But even after termination of experienced bullying victimization during a bullying prevention program, individuals lacked full recovery from mental health problems and presented with ongoing reduction of quality of life. Interestingly, we did not observe a decline in psychopathology despite successful implementation of bullying prevention (Ossa et al, 2020). While bullying declined from 8.00% to 5.11% within two years, the observed level of emotional problems, total difficulties, non-suicidal self-injury, and suicidality remained relatively stable.…”
Section: Discussioncontrasting
confidence: 55%
“…For details about the recruitment procedure and the program components, we refer to Ossa et al. (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the effects of an intervention on child-reported proactive aggression were shown to differ as a function of participants' gender, with stronger effects for boys (Stoltz et al, 2013; see also Kennedy, 2020). Other studies evaluating the effectiveness of aggression interventions reported that girls profited more (e.g., Ossa et al, 2020), while still others did not find gender to be a statistically significant moderator (see e.g., Hendriks et al, 2018). Testing for potential moderating effects of gender, as a key socio-demographic characteristic, is always relevant, as it clarifies whether the same program is equally adaptive for all participants irrespective of gender; however, the mixed current body of research makes it difficult to derive clear predictions about the role of gender for the current aggression prevention program's functioning.…”
Section: Individual Student Characteristicsmentioning
confidence: 99%
“…In addition, school-based prevention, which has shown to be an effective method of suicide prevention (e.g., [33]), may set a stronger focus on school climate and peer relationships. As an example, reduction of bullying via so-called whole school approaches (e.g., [21]) may also reduce suicide risk in adolescents.…”
mentioning
confidence: 99%